POTENTIAL PROTECTIVE EFFECT OF APOCYNIN IN ETHYLENE GLYCOL-INDUCED HEPATIC DAMAGE BY ATTENUATION OF MITOCHONDRIAL OXIDATIVE STRESS - Kumari, Sumeeta; Sharma, Minu; Singla, S.k. (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present study was carried out to investigate the protective role of apocynin (APO), an nicotinamide adenine dinucleotide phosphate oxidase inhibitor, against ethylene glycol (EG)-induced hepatotoxicity in rats. Methods: Male Sprague-Dawley rats were divided into three groups with six animals in each group. Control group; EG group, in which hyperoxaluria was induced by 0.4% EG in drinking water for 9 days; and EG+APO group, 0.4% EG in drinking water for 9 days along with APO at a dosage of 200 mg/kg body weight/day, intraperitoneal. All the experimental animals were sacrificed on day 10. Serum and the liver homogenates were analyzed for various biochemical parameters. Mitochondria from liver were isolated by differential centrifugation and were diagnosed for vital biochemical parameters. Results: Hyperoxaluric animals have shown significantly increased levels of serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, alkaline phosphatase, and lactate dehydrogenase, thus suggesting liver dysfunction. Declined activities of respiratory chain enzymes showed mitochondrial dysfunction in EG treated rats. In addition, mitochondrial oxidative stress was evident by decreased levels of superoxide dismutase, reduced glutathione, and an increased lipid peroxidation (LPO). APO (200 mg/kg/day), significantly decreased EG-induced oxidative stress by reducing LPO and restoring antioxidant enzymes activities in liver tissue. Also, reduction in the impairment of liver mitochondria functioning was detected in APO treated rats. Histological analysis depicted that APO treatment decreased liver epithelial damage, increased Kupffer cells, and restored normal hepatocyte morphology. Conclusion: The results demonstrated the potential beneficial effects of APO in reducing EG-induced liver damage that might be through attenuation of mitochondrial oxidative stress. Keywords: Ethylene glycol, Liver, Oxidative stress, Mitochondrion, Apocynin, Antioxidant.